Analysis of Packaging Raw Material Requirements in Inventory Management PT. XYZ - Larasati, Mentari; Madelan, Sugiyono; Saluy, Ahmad Badawi (Dinasti Publisher, 2021)
This study aims to determine the grouping of packaging raw material inventory and inventory planning that can minimize the total inventory cost of packaging raw materials at PT. XYZ. The population in this study is secondary data in the form of purchasing, production, and supply of packaging raw materials with sample data as much as the period January 2020 - December 2020. Data analysis methods used Minitab software and POM QM. The results show that the EOQ method can save the total inventory cost of fast moving-vital product in 2021 is Rp. 143,066 with the total number of requests being 1,227,214 pcs higher than the company's current method.